(untitled) - Arnold, Stephanie (Mountain View, Calif., 2001)
This introductory text provides coverage of the broad range of contemporary theatre and includes complete scripts of five plays: August Wilson's Joe Turner's Come and Gone, Wakako Yamauchi's And the Soul Shall Dance, Tony Kushner's Angels in America, Marsha Norman's Getting Out, and Sam Shepard's Buried Child. The text emphasizes the collaborative and creative processes that go into productions, and includes interviews with theatre artists.
Keywords: Theater,Drama